Anatomical variations in pneumatization types and volume of sphenoid sinus in a subset of Pakistani people - Aijaz, Asma; Naheed Khan (Journal of the Pakistan Medical Association, 2024)
Objective: To evaluate the relationship between volume and pneumatization pattern of sphenoid sinus using computed tomography images. Method: The prospective, cross-sectional study was conducted at the Radiology Department of Dow University of Health Sciences, Karachi, from October 2020 to February 2021, and comprised patients of either gender aged 20-70 years who were subjected to computed tomography of paranasal sinuses. The scans were analysed for sphenoid volume and four pneumatization types of sphenoid sinus, including Type-I conchal, Type-II presellar, Type-III sellar and Type-IV postsellar. Significant differences in sphenoid volume and pneumatization pattern were noted. Data was analysed using GraphPad Prism 9. Results: Of the 300 patients with mean age 39.28±10.99 years171(57%) were males and 129(43%) were females. The mean sphenoid volume in males was 11.01±3.50cm3 compared to 7.7±2.13cm3 in females. The majority of sinuses presented postsellar pneumatization type 192(64%), followed by sellar 84(29%), presellar 26(8.7%) and conchal pneumatization 2(0.7%). Significant difference in volume was observed with respect to gender and typology of the sphenoid sinus (p<0.001). Conclusion: There was a significant relationship of sphenoid volume with and gender and pneumatisation variants, confirming the significance of ethnic heterogeneity. Key Words: Paranasal sinuses, Sphenoid bone, Sphenoid sinus, Computed tomography.